Development of interactive e-module based on video and augmented reality for earthquake technology course - Budi, Listiyono; Widodo, Aris; Julianto, Eko Nugroho; Dermawan, Moch Husni; Mayasari, Retno; Chonora, Angelique; Soraya, Angelia Nilam; Ardiansah, Ridwan (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The implementation of augmented reality and video in instructional media is highly suitable for courses in the field of civil engineering, one of them is the Earthquake Technology. This research employed the Research and Development (R&D) method using the ADDIE model in developing the e-module. The result of this research is an e-module specifically designed for the Earthquake Technology courses. The e-module was validated by media experts, subject matter experts, and students as part of the evaluation process. The average scores from the two media experts were 93.33 and 91.33 for graphic feasibility, and 96.67 and 93.33 for language feasibility. As for the two subject matter experts, the average scores for content feasibility were 89.41 and 88.24, for presentation feasibility were 87.50 and 90.00, and for contextual feasibility were 90.00 and 90.00. Meanwhile, the average score from the students during the pilot study was 89.06. The results of this research indicate that the development of the Earthquake Technology e-module using the ADDIE method has resulted in an e-module with "very good" category in terms of media and "good" category in terms of content. The assessment results from students also indicate that the Earthquake Technology e-module falls into the "good" category. So, it can be concluded that the Earthquake Technology e-module based on video and augmented reality can be totally implemented in the learning process of Earthquake Technology course at higher education institution.